OVERCOMING VITAMIN-D DEFICIENCY IN MALE GYMNASTS DURING PRETEEN YEARS - Syed Arif Kamal; Shahid Ali Khan (The Sky)
This paper addresses the issue of vitamin-D deficiency, which is approaching epidemic scale in the Asian countries. Lack of proper nutrition and awareness contributes to this problem. After an explanation of the mechanism of production of vitamin D, the authors list adverse effects of vitamin-D deficiency and propose mandatory testing of vitamin-D deficiency during physical examinations. The remedial measures to overcome this deficiency in the context of preteen male gymnasts include supplements, proper nutrition in the form of sun-ripe fruits and vegetables as well as guarded-graduated sun-exposure. The last two are preferred over supplements as the supplements may produce toxicity if taken in higher doses.